2006
DOI: 10.1007/s10569-005-2288-9
|View full text |Cite
|
Sign up to set email alerts
|

Linear Stability of the Lagrangian Triangle Solutions for Quasihomogeneous Potentials

Abstract: In this paper, we study the linear stability of the relative equilibria for homogeneous and quasihomogeneous potentials. First, in the case the potential is a homogeneous function of degree −a, we find that any relative equilibrium of the n-body problem with a > 2 is spectrally unstable. We also find a similar condition in the quasihomogeneous case. Then we consider the case of three bodies and we study the stability of the equilateral triangle relative equilibria. In the case of homogeneous potentials we reco… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 14 publications
0
7
0
1
Order By: Relevance
“…Note that further studies on the stabiltiy of the equilateral configuration as a function of κ can be found in Santoprete (2006). The value of μ G = m 2 /(m 1 + m 2 ) = (1 − √ 23/27)/2 = 0.03852 .…”
Section: Introductionmentioning
confidence: 93%
“…Note that further studies on the stabiltiy of the equilateral configuration as a function of κ can be found in Santoprete (2006). The value of μ G = m 2 /(m 1 + m 2 ) = (1 − √ 23/27)/2 = 0.03852 .…”
Section: Introductionmentioning
confidence: 93%
“…The equations of motion of the infinitesimal mass in the rotating coordinate system are written as (see, for example, Papadouris and Papadakis, [17] 2 ,…”
Section: Equations Of Motionmentioning
confidence: 99%
“…Later, Routh [19] studied the linear stability of the same solutions in the case of homogeneous potentials. Recently, Papadouris and Papadakis [17] produced the necessary condition for the stability of the Lagrange central configuration in the photogravitational R4BP based on the ideas of Santroprete [20] and Moeckel [21]. Based on these ideas, if someone replaces the masses…”
Section: Linear Stability Of the Lagrange Configurationmentioning
confidence: 99%
See 1 more Smart Citation
“…The general problem was made precise by Andoyer [12]. Particular cases have been studied for three bodies [50,117,115,121], four bodies [111,22,116,135], restricted cases (i.e. with one or more infinitesimal masses) [107], and polygonal and N + 1 ring systems [53,125,96,114,26,19]; more could be done, especially numerically, in our setting of a variable exponent potential.…”
Section: Introductionmentioning
confidence: 99%